(untitled) (New Jersey, 2004)
This book makes a global survey of nonperturbative aspects of quantum chromodynamics (QCD) from the viewpoints of mathematical, elementary-particle and hadron physics, including recent lattice-QCD results. It presents current, important progress in the following areas: the quark confinement mechanism, dynamical chiral-symmetry breaking, topologies in QCD (instantons, monopoles, vortices), SUSY QCD, nonperturbative methods (1/Nc, ladder QCD, AdS/CFT), QCD phase transition at finite temperature and density, quark–gluon plasma, and so on. For recent topics, the book also includes the experimental discovery of the penta-quark particle, the newest information on the QGP creation experiments, and theoretical progress on the baryonic three-quark potential and the high-density QCD.
Keywords: Color confinement (Nuclear physics),Quantum chromodynamics,Sự sản xuất màu ( vật lý hạt nhân )